En savoir des choses : une étude de davar ‘chose’ dans un corpus d’hébreu parlé - Silvia Adler; Il-Il Yatziv-Malibert (Studii de Lingvistica)
Based on the CoSIH Corpus of spoken Israeli Hebrew, our study aims at examining the syntactic and pragmatic roles, in spoken Hebrew, of the seemingly meaningless lexeme davar ‘thing’. Our case study could therefore extend the reflection on general nouns and unspecified nouns of which davar and thing are a part. The studies already conducted on chose in French will help us to understand the affinities as well as the idiosyncrasies of davar in relation to its French counterpart. On the other hand, the works on thing emanating from the Anglo-Saxon tradition will allow us to consolidate the functioning of davar as a general noun in search of a context.